2015
DOI: 10.3390/ijms160715442
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-Derived Neurotoxin (EDN/RNase 2) and the Mouse Eosinophil-Associated RNases (mEars): Expanding Roles in Promoting Host Defense

Abstract: The eosinophil-derived neurotoxin (EDN/RNase2) and its divergent orthologs, the mouse eosinophil-associated RNases (mEars), are prominent secretory proteins of eosinophilic leukocytes and are all members of the larger family of RNase A-type ribonucleases. While EDN has broad antiviral activity, targeting RNA viruses via mechanisms that may require enzymatic activity, more recent studies have elucidated how these RNases may generate host defense via roles in promoting leukocyte activation, maturation, and chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 74 publications
3
76
0
Order By: Relevance
“…The precise mechanisms through which the exosomes of T lymphocytes trigger b cell death remain to be fully established. In vitro, activation of NF-kB signaling as well as the induction of several members of the Ear family that are cytotoxic in other cell types (Gupta et al, 2013;Rosenberg, 2015) may contribute to the increase in the apoptotic rate observed upon exposure to exosomes. In vivo, T lymphocyte exosomes may be part of the mechanisms favoring islet inflammation, insulitis progression, and T1D development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise mechanisms through which the exosomes of T lymphocytes trigger b cell death remain to be fully established. In vitro, activation of NF-kB signaling as well as the induction of several members of the Ear family that are cytotoxic in other cell types (Gupta et al, 2013;Rosenberg, 2015) may contribute to the increase in the apoptotic rate observed upon exposure to exosomes. In vivo, T lymphocyte exosomes may be part of the mechanisms favoring islet inflammation, insulitis progression, and T1D development.…”
Section: Discussionmentioning
confidence: 99%
“…The array data revealed also a strong increase in the level of the eosinophil-associated ribonuclease family members, Ear1, Ear2, and Ear12 (Table S2). The role of these RNases in b cells has so far not been explored but, in other cell types, Ear proteins have cytotoxic and chemoattractant effects (Gupta et al, 2013;Rosenberg, 2015). Interestingly, overexpression of miR-142-3p/-5p and miR-155 in mouse islet cells led to an increase in the level of Ccl2, Ccl7, and Cxcl10 similar to that observed upon incubation with exoNOD ( Figure 5C), indicating that at least part of the effect of the exosomes is mediated by the transfer of these miRNAs.…”
Section: T Lymphocyte Exosomes Promote B Cell Apoptosis and Induce Thmentioning
confidence: 99%
“…Eosinophil‐derived neurotoxin is a major secretory protein of the eosinophils . These granulocytes are readily detectable throughout the human gut in normal conditions, and their numbers are increased in both colorectal mucosa and colorectal mucus of IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophil-derived neurotoxin is a major secretory protein of the eosinophils. 23 These granulocytes are readily detectable throughout the human gut in normal conditions, 37 and their numbers are increased in both colorectal mucosa 38,39 and colorectal mucus 22 of IBD patients. Our observation of EDN abundance in the latter material confirms eosinophil participation in the inflammatory process, which involves both the mucosa and the protective mucus barrier overlaying it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation